Tamoxifen for women at high risk of breast cancer - Nazarali SA (Dove Medical Press, 2014)
Safia A Nazarali, Steven A Narod Women's College Research Institute, Women's College Hospital, and The University of Toronto, Toronto, Ontario, Canada Abstract: Tamoxifen has been used as a treatment for women who have been diagnosed with breast cancer for roughly four decades and has been approved as chemoprevention for over ten years. Although tamoxifen has been proven to be beneficial in preventing breast cancer in high-risk women, its use has not been widely embraced. To some extent, this is due to several of its side effects, including an increased risk of endometrial cancer and pulmonary embolism, but these serious side effects are rare. The risks and benefits of tamoxifen chemoprevention should be considered for each patient. Keywords: tamoxifen, breast cancer, women, chemoprevention